KETAHANAN PANGAN RUMAH TANGGA PETANI ANGGOTA LUMBUNG DI KECAMATAN GADING REJO, KABUPATEN PRINGSEWU - Marita Infia Fitriani; Fembriarti Erry Prasmatiwi; Rabiatul Adawiyah (Lampung University, 2020)
This study aims to analyze food security level, the factors affecting food security, and the efforts to increase food security of farmer household of granary member. The location of this study is chosen purposively as consideration that the group of granaries received the granary development program in Gading Rejo Subdistrict, Pringsewu Regency with 44 farmers of granary members who are selected by proportional random sampling method. Data were collected in April 2018. Food security level is analyzed using cross classification between food expenditure and food sufficiency level, factors affecting the level of food security is analyzed using ordinal logistic regression, and the efforts to increase the level of food security is analyzed using descriptive qualitative analysis. The study shows that food security according to BPS category as much as 22.,73% is in secure category, 15.91% less secure, 34.09% vulnerable, and 27.27% insecure. Food security according to nutrition science and the 2012 Constitution of Food as much as 45.45% is in secure category, 27,27% less secure, 15.91% vulnerable, and 11.36% insecure. Factors that influence the level of food security are rice production, price of rice, and side occupation. Efforts to increase food security are programs on increasing income through irrigation and crop indexes, improving nutrition through education on nutrition and food by the government, accelerating food diversification, and development of food barns. Farmer’s effort to overcome food shortages is by changing habit in the quality of food consumed.Key words: food security, granary member